2023
DOI: 10.1186/s12943-023-01804-z
|View full text |Cite
|
Sign up to set email alerts
|

Exosome-mediated miR-144-3p promotes ferroptosis to inhibit osteosarcoma proliferation, migration, and invasion through regulating ZEB1

Abstract: Background Osteosarcoma (OS) is the most prevalent orthopedic malignancy with a dismal prognosis. The high iron absorption rate in OS cells of patients suggests that ferroptosis may be related to the progression of OS, but its potential molecular regulatory role is still unclear. Based on the ability to couple with exosomes for targeted delivery of signals, exosome-derived micro ribonucleic acids (miRNAs) can potentially serve as diagnostic biomarkers for OS. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Notable genes with frequent alterations included ITGA8 (9%), ZEB1 (7%), ZEB2 (6%), among others, exhibiting a range of mutation types from missense to frameshift deletions. These genes were proved to relate with programed cell deaths and cancer immune in previous studies 24 26 .
Figure 2 Overview of necrotic anoikis-related gene alterations in lung adenocarcinoma.
…”
Section: Resultsmentioning
confidence: 92%
“…Notable genes with frequent alterations included ITGA8 (9%), ZEB1 (7%), ZEB2 (6%), among others, exhibiting a range of mutation types from missense to frameshift deletions. These genes were proved to relate with programed cell deaths and cancer immune in previous studies 24 26 .
Figure 2 Overview of necrotic anoikis-related gene alterations in lung adenocarcinoma.
…”
Section: Resultsmentioning
confidence: 92%
“…Apart from leading to changes in cell death, ferroptosis can affect many other functions of cancer cells, including migration/metastasis, invasion, drug resistance, metabolism and immune escape. Inhibition of ferroptosis has been demonstrated to be associated with increased migration, invasion and metastasis of multiple cancer cells, such as renal cell carcinoma, gastric cancer and osteosarcoma 17–20 . In pancreatic cancer, inhibition of ferroptosis has also been regarded as an effective strategy to suppress cell migration and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…99 In addition, Jiang et al used exosomes from Osteosarcoma (OS) as carriers of miRNA-144-3p to promote ferroptosis and inhibit the proliferation, migration and invasion of osteosarcoma by regulating ZEB1. 100 Wu et al . by selecting WT, Fcna−/− and Fcnb−/− mice to construct bleomycin (BLM)-induced lung injury model, found that Ficolin B (Fcn B), which is transported by AMs exosomes, promotes ferroptosis of lung epithelial cells through cGAS-STING signaling pathway, thus aggravating BLM-induced lung injury.…”
Section: Application Of Ferroptosis-based Nanomedicine Delivery Syste...mentioning
confidence: 99%